Develoment of education - Minis, Mary Frances (My University, 1898)
Introduction: In this review will be given only the chief influences that have affected education, together with a few of the teachers and leading methods of instruction. Education is not an element of civilization alone, but it has existed during the whole period of human life, and may even be traced to the lower animals, among which have often been noticed efforts to instruct their young. It is characteristic of the savage and barbarous ages. Perhaps from the time of the first human family, from the time when parents began to lore their children, education had an existence. There were no organized methods of instruction, yet education, even in this crude stage, is of high value. It places a child at maturity in possession of the mental development of all the ages. There have been given to him facts that have taken the world ages to reach and it represents the work of the best minds and greatest men of history. Education, therefore, has been a great agent in the evaluation of the human mind. The thinkers of mankind in the early ages turned toward the church, which monopolized all the learning, and they kept hold of this powerful force for a long time; and even yet in some countries this hold is not relaxed. Priests are not naturally conservative, and it is apparent that if the priests had not kept such a firm hold upon education that it would have spread much quicker than it did.
Citation: Minis, Mary Frances. Develoment of education. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Education; Civilization; Mental Development; Theses; Manuscripts (documents)